Influence of Structural Characteristics on the Mechanical Properties of FDM Printed PLA Material - Szczepanik, Stefan; Nikiel, Piotr (Journal of Casting & Materials Engineering, 2020)
The present study reports on the influence of printing process parameters, architecture, raster, infill orientation and filling on the density, macrostructure, and mechanical properties, including impact resistance, of biodegradable polymer parts fabricated in polylactide (PLA) on a desktop printer. It complements and considers phenomenologically the results of recently published similar studies, including the use of recycled filament. In our study, complex mechanical properties for the samples printed at the same time on a Replicator 2 printer were investigated. Three samples were printed for each test. Full mechanical characteristics (tensile, compression and bend strengths and impact resistance) of the printed PLA material are reported. This is the novelty in comparison to other studies, where the samples test were printed individually or in a series for each test. The shape and thickness of the layered macrostructure, the presence of holes inside the layers, the number of shell perimeters and the fill density all influenced the tensile properties of the printed materials. These results show the possibility of printing with a 0.3, i.e. shorter printing time than 0.1, 0.15 and 0.18 mm layer thicknesses also reported, without significant decrease in mechanical properties. It is interesting to note that the compressive strengths, the yield of 70–80 MPa and a UTS 113–120 MPa for the printed material with a fill density of 94–96% are comparable with those of aluminum.